2019
DOI: 10.1038/s41598-019-53994-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical detection of different p53 conformations by using nanostructured surfaces

Abstract: Protein electrochemistry represents a powerful technique for investigating the function and structure of proteins. Currently available biochemical assays provide limited information related to the conformational state of proteins and high costs. This work provides novel insights into the electrochemical investigation of the metalloprotein p53 and its redox products using label-free direct electrochemistry and label-based antibody-specific approaches. First, the redox activities of different p53 redox products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…When Aβ is present at nanomolar levels, throughout the inhibition of HIPK2, it induces the expression of metallothionein 2A, which, endowed with Zn-chelating activity, sequesters metals from the DNA-binding-domain of p53 and induces its conformational changes, which in turn inhibits its activity [ 21 ]. In addition, a low-grade pro-oxidant environment, instead activating p53 intracellular pathways, affects its tertiary structure, inducing conformational changes and the loss of its activity [ 13 , 52 , 53 ]. Since p53 regulates a heterogeneous repertoire of biological functions [ 43 , 44 ], including neuronal outgrowth and neuronal connectivity protection [ 14 , 21 ], regulation of innate immunity [ 54 ], and redox homeostasis [ 21 , 55 , 56 ], we hypothesize that the expression of this conformational variant in the early stage of the disease might contribute to synapse dysfunction, inflammation, and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When Aβ is present at nanomolar levels, throughout the inhibition of HIPK2, it induces the expression of metallothionein 2A, which, endowed with Zn-chelating activity, sequesters metals from the DNA-binding-domain of p53 and induces its conformational changes, which in turn inhibits its activity [ 21 ]. In addition, a low-grade pro-oxidant environment, instead activating p53 intracellular pathways, affects its tertiary structure, inducing conformational changes and the loss of its activity [ 13 , 52 , 53 ]. Since p53 regulates a heterogeneous repertoire of biological functions [ 43 , 44 ], including neuronal outgrowth and neuronal connectivity protection [ 14 , 21 ], regulation of innate immunity [ 54 ], and redox homeostasis [ 21 , 55 , 56 ], we hypothesize that the expression of this conformational variant in the early stage of the disease might contribute to synapse dysfunction, inflammation, and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that p53 conformational alterations were found in different cell types derived from AD patients (fibroblasts, immortalized B lymphocytes, and peripheral blood mononuclear cells (PBMCs)) as well as in in vitro and in vivo models [ 11 , 12 ], using several experimental approaches. More recently, we demonstrated that, upon different redox stressors exposure, several misfolding p53 conformations can exist [ 13 ] with different affinity for different anti-p53 antibodies. Here, we propose the detection in plasma of a misfolding p53 conformational variant recognized by the novel conformational antibody 2D3A8 (U-p53 2D3A8+ ) as a predictive biomarker of AD risk.…”
Section: Introductionmentioning
confidence: 99%
“…The use of nano-cubes of novel graphene-based nanostructures, realized with a combination of different materials [92], to enhance cell-biosensor interaction [93], and of printed nanostructures combined with novel curing techniques, have been highlighted in the recent literature as promising to improve the performance of paper-based biosensors [94]. Furthermore, in [95,96], specific comparisons in terms of sensitivity were performed among carbon nanotubes, as well as fullerene and platinum printed nanostructured electrochemical sensors, demonstrating the combined effect of the chemistry, shape, dimension and deposition techniques of the nanostructures on LOD and repeatability. An improvement in the LOD in quantifying IL-8 (from 2 ng/mL to 0.38 ng/mL) and p53 proteins (from 2 ug/mL to 100 ng/mL) could be obtained with nanostructured biosensors with respect to their non-nanostructured counterparts.…”
Section: Printed Nanostructures To Improve Lod Sensitivity and Repeatabilitymentioning
confidence: 99%
“…This approach is based on the use of redox tracers which can be quantitatively measured exploiting electron transfer processes that happen at the interface of dedicated electrodes on the LFIA membrane. EC-LFIA systems have been reported in literature based on amperometric, voltammetric and impedimetric detection methods [42,43]. In addition, integration of electrodes on the LFIA strip enabled the use of electrochemiluminescent (ECL) tracers for ECL-LFIA applications, providing high sensitivity, wide detection range and high reproducibility [44].…”
Section: Introductionmentioning
confidence: 99%